Effectiveness of cardiac telerehabilitation with relapse prevention compared to centre-based cardiac rehabilitation: results from the SmartCare-CAD randomised controlled trial. (11th May 2021) - Brouwers, R; Kraal, JJ; Regis, M; Spee, RF; Kemps, HMC
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This study was part of the SmartCare project, which was partially funded under the ICT Policy Support Programme (ICT PSP), grant agreement number 325158. Background: Most studies failed to show superiority of cardiac telerehabilitation (CTR) over traditional, centre-based cardiac rehabilitation (CR). Purpose: To evaluate the effectiveness of a novel CTR intervention on the adherence to a physically active lifestyle in patients with coronary artery disease (CAD). Methods: We randomised patients with CAD entering phase II outpatient CR to either CTR with relapse prevention by on-demand coaching (intervention group), or centre-based CR with supervised exercise training (control group). The primary outcome measure was objectively assessed physical activity level (PAL), secondary outcome measures included physical fitness and quality of life (QoL). Results: A total of 300 patients (89% male, mean age 60.7 ± 9.5 years) participated in the trial. Both groups significantly improved their PAL at 12 months follow-up (p < 0.01), but without a significant between-group difference in the response over time (p = 0.73). Similarly, we observed sustained increases in physical fitness and QoL, but without significant between-group differences in responses over time. Conclusions: In patients with CAD who had low residual cardiovascular risk, CTR with relapse prevention resulted in a sustained increase in PAL, physical fitness and QoL, but without differences in responses over time as compared to centre-based CR. For this reason, future CTR interventions should be directed specifically to patients who are at risk for relapse into unhealthy lifestyle behaviour.